Enzymatic Hydrolysis of Pretreated Fibre Pressed Oil Palm Frond by using Sacchariseb C6 - Fatin Syazwana, Hashim; Wan Mohd Hafizuddin, Wan Yussof; Mior Ahmad Khushairi, Mohd Zahari; Roshanida, A. Rahman; Rosli, Md. Illias (IOP Publishing, 2017)
Enzymatic hydrolysis becomes a prominent technology for conversion of cellulosic biomass to its glucose monomers that requires an action of cellulolytic enzymes in a sequential and synergistic manner. In this study, the effect of agitation speed, glucan loading, enzyme loading, temperature and reaction time on the production of glucose from fibre pressed oil palm frond (FPOPF) during enzymatic hydrolysis was screened by a half factorial design 25-1 using Response Surface Methodology (RSM). The FPOPF sample was first delignified by alkaline pretreatment at 4.42 (w/v) sodium hydroxide for an hour prior to enzymatic hydrolysis using commercial cellulase enzyme, Sacchariseb C6. The effect of enzymatic hydrolysis on the structural of FPOPF has been evaluated by Scanning Electron Microscopy (SEM) analysis. Characterization of raw FPOPF comprised of 4.5 extractives, 40.7 glucan, 26.1 xylan, 26.2 lignin and 1.8 ash, whereas for pretreated FPOPF gave 0.3 extractives, 61.4 glucan, 20.4 xylan, 13.3 lignin and 1.3 ash. From this study, it was found that the best enzymatic hydrolysis condition yielded 33.01 ± 0.73 g/L of glucose when performed at 200 rpm of agitation speed, 60 FPU/mL of enzyme loading, 4 (w/w) of glucan loading, temperature at 55 squ and 72 hours of reaction time. The model obtained was significant with p-value <0.0001 as verified by the analysis of variance (ANOVA). The coefficient of determination (R2) from ANOVA study was 0.9959. Overall, it can be concluded that addition of Sacchariseb C6 during enzymatic hydrolysis from pretreated FPOPF produce high amount of glucose that enhances it potential for industrial application. This glucose can be further used to produce high-value products.